Pemanfaatan Tanaman Obat Keluarga (TOGA) dalam Pencegahan Stunting: Pendekatan Edukatif dan Manajemen Hidup Sehat - Novia Safitri; Fatiah Rahmah; Milawati Valantia; Santi Santi; Yuni Amalia; Solehudin Solehudin; Try Adhi Bangsawan (Lembaga Pengembangan Kinerja Dosen, 2024)
The use of Family Medicinal Plants (TOGA) as a form of approach in stunting prevention has become the main focus of the community service program in Curug Village, Mekar Agung Village. This program intends to increase public knowledge and skills in utilizing TOGA in preventing and reducing the prevalence of stunting in toddlers. The approach used is educational, through socialization and training to mothers at posyandu. The results of this activity have an impact on increasing public awareness and understanding of the importance of balanced nutrition and the role of TOGA in supporting children's health. In addition, this program has also succeeded in building a community that cares more about health issues, especially in efforts to prevent stunting. The implementation of this program involves cooperation between midwives, posyandu cadres, and students, who directly assist the community in implementing TOGA as part of a healthy lifestyle. Thus, this activity is expected to be a model and applied in other regions to reduce stunting rates and improve the quality of public health.